Primary pleomorphic liposarcoma of the spine. Case report and review of the literature - Morales-Codina, A.M. (Int J Surg Case Rep, 2016)
INTRODUCTION: To describe a single case, the fourth ever reported, of pleomorphic liposarcoma of the spine and to undertake a review of the literature. PRESENTATION OF CASE: A 60 year old male patient had a bilateral lumbosciatica over a 3 month period. Imaging tests revealed a tumor mass in L1–L3 and a fracture in L2. Also, he had a mural thrombus both in the inferior vena cava and the left renal vein. The biopsy revealed a well-differentiated liposarcoma. En bloc resection of the lesion and stabilization was carried out. Due to the condition of the patient (hemodynamic instability, wound dehiscence and infection, and hypoproteinemia), a decision was made not to subject the patient to either radiation therapy or chemotherapy. The patient was subsequently found to suffer from myopathic paraparesis and a surgical wound infection. At three months, liver metastases were evident, as well as a recurrence of the lesion. A venous thrombosis that extended from the lower iliac vein to the right atrium was observed. The patient died from type I hepatorenal syndrome. DISCUSSION: Pleomorphic liposarcoma of the spine is a rare occurrence. En bloc resection with wide margins is the treatment of choice. The use of radiotherapy in the spine is controversial. The role that should be played by chemotherapy is still unclear, although it has been employed in treatments. CONCLUSION: In spite of treatment, these tumors lead to a poor prognosis, with high rates of recurrence, metastasis, and mortality.